Desain User Interface Aplikasi GSSHOP Dengan Menggunakan Metode Lean UX - Wibowo, Adrian Ravaliano; Kuswoyo, Deni; Rahmansyah, Nur (Universitas Multi Data Palembang, 2025)
Mobile applications have become a crucial part of the digital world, especially in the gaming industry. GSSHOP is a platform that provides various gaming products, from consoles and games to accessories, along with features like vouchers, points, and repair status. This research focuses on evaluating and improving the usability and user experience (UX) of the GSSHOP app. Although it has been downloaded by many users, the low rating on the Play Store indicates significant issues with its UI/UX. The initial survey using the System Usability Scale (SUS) with 40 participants showed an average score of 37.625, which falls in the low category. This suggests that the app is not meeting the users' needs. This study will focus on redesigning the UI to improve the SUS score and address usability issues, such as difficult navigation and unclear product information. The goal is to provide user-centered UI design recommendations that could improve user satisfaction, boost the Play Store rating, and support the growth of the GSSHOP business.